1 1,8(-3) + 0,6x
2.
m-(-0,75n)-(-0,6k)
3
2(a+b)
4
5
6
0,4(a +3)
2.m-(-3)
6.n. (-5)
9x-(-7)+5x
4y.(-10)+3y
16x.(-2)+21%
7
co
9
10
8a-4b-(-6)
11
m.(-62n)-(-2)
12.
-2x 74.(-2)​


1 1,8(-3) + 0,6x2.m-(-0,75n)-(-0,6k)32(a+b)4560,4(a +3)2.m-(-3)6.n. (-5)9x-(-7)+5x4y.(-10)+3y16x.(-2

FrutikFresh FrutikFresh    2   24.12.2020 16:49    1

Ответы
1970msa 1970msa  23.01.2021 16:50

1,8(-3)+0,6х

-54+0,6х=0

0,6х=54

х=-90

2.m(-0,75)*(-0,6k)=0,45mk

3.2(a+b)=2a+2b

4.0,4(a+3)=,0,4a+1,2

5.2m(-3)=-6m

6.-6n(-5)=30n

7.9x(-7)+5x=-63x+5x=-58x

8.4y(-10)+3y=-40y+3y=-37y

9.16x(-2)+21x=-32x+21x=-11x

10.8a4b(-6)=-192ab

11.m(-62n)(-2k)=124mnk

12.-2x7y(-z)=14xyz

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра